A reflection on social science teachers' pedagogical content knowledge and its implications for learner performance : a case of schools in Mpumalanga Province, South Africa - Mashiloane, David Mathabi (My University, 2023)
Refer to the document
Thesis (M. Ed. (Curriculum Studies)) -- University of Limpopo, 2023
Keywords: Social sciences; Teachers; High school education; Social sciences; Social sciences -- Study and teaching (Secondary) -- South Africa; Education -- Curricula -- South Africa; Academic achievement; Pedagogical content knowledge